Optical Features of Vapor‐Phase Epitaxial Re‐Grown Long Semiconducting Single‐Walled Carbon Nanotubes. Issue 9 (21st February 2019) - Fedotov, Pavel V.; Chernov, Alexander I.; Obraztsova, Ekaterina A.; Obraztsova, Elena D.
Abstract : The monodispersed long single‐wall carbon nanotubes (SWCNTs) with controlled morphology are promising in various research fields and many applications, such as optoelectronics, nanoelectronics and recently upon utilizing them as nanoreactors. In this work the long aligned semiconducting single‐walled carbon nanotubes as well as the extended semiconducting nanotube networks are synthesized via a vapor‐phase epitaxial (VPE) cloning growth method. The semiconducting nanotubes are grown on ST‐cut quartz substrates using acetylene and ethanol as a precursors from the seeds of sorted SWCNTs. According to the conducted study the length of the grown nanotubes can reach up to 70 μm. The extensive optical study confirms the preservation of SWCNTs chirality during re‐growth from nanotube seeds and the high quality of the obtained long semiconducting nanotubes. Polarization dependent Raman demonstrates the high alignment degree of the re‐grown SWCNTs. In dense growth regime SWCNTs demonstrate strong Raman response due to the smaller amount of defects. Such networks of SWCNTs can be a good candidate for optoelectronic applications. Abstract : In this work, long aligned semiconducting single‐walled carbon nanotubes (SWCNTs) as well as extended semiconducting nanotube networks are synthesized via a vapor‐phase epitaxial growth method. The length of the grown nanotubes can reach up to 70 µm. The extensive optical study confirms the preservation of SWCNTs chirality during re‐growth from nanotube seeds and the high quality of the obtained long semiconducting nanotubes.